INVESTMENT ENVIRONMENT AND UZBEKISTAN’S ACCESSION TO THE WTO (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Uzbekistan stands at a pivotal juncture in its post-independence economic history. Since 2016, the country has undergone sweeping market reforms that have transformed it from one of Central Asia’s most closed economies into an increasingly open investment destination. WTO accession, targeted for the 14th Ministerial Conference (MC14) in March 2026, represents the capstone of this transformation. With 33 of 34 bilateral negotiations completed by late 2025 and 192 pieces of legislation submitted for WTO review, Uzbekistan is closer to membership than at any point since its initial application in 1994. Economic modeling suggests WTO accession could add 0.4 percentage points to annual GDP growth through tariff liberalization alone, while services-sector opening could generate gains of up to 17% of real GDP over the longer term. This article examines the interplay between Uzbekistan’s evolving investment climate and its WTO accession trajectory, drawing on official WTO documents, World Bank and OECD reports, and comparative analysis of post-Soviet accession experiences in Kyrgyzstan, Tajikistan, Kazakhstan, and Russia.